Study on incidences of electrolyte disorders among children with dehydration - Dr. G. Kalyan Chakravarthi; Dr. R. Praveen Kumar (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Electrolyte abnormalities are common in children with diarrhoea. It may remain unrecognized and result in mortality and morbidity. Timely recognition, a high index of suspicion and thorough understanding of common electrolyte abnormalities is necessary to ensure their correction. The present work was undertaken to determine the incidence and clinical importance of Hypokalemia, hypernatraemia, Hyponatremia and Hypernatremia in children with acute diarrheal diseases with dehydration.Method: The present prospective study was conducted at Department of Paediatrics, GSL Medical College & General Hospital, Rajahmundry from 2015 to 2017.Consecutive Patients attending OPD and inpatients in view of acute diarrhea between 1month and 5years of age were included in the study. A detailed history from the patients with acute gastroenteritis of age 1 month to 5 years was taken.Result: The incidence of Acute diarrhoea was greater in males (54.6%%) compared to females (45.4%). Severe Dehydration was present in 39.1% cases and some dehydration was present in 60.8% cases. Hyponatremic dehydration was present in 33% cases, Isonatremic dehydration in 59.8% and hypernatremic dehydration in 7.2% cases. Mean sodium levels being 134.97 mmol/l. Hypokalemia was present in 44.3% cases, normal levels in 51.6% and Hyperkalemia in 4.2% cases. Mean potassium levels being 3.62 mmol/l.Conclusion: Like any other electrolyte abnormalities, which occurs in conditions other than diarhoea, are basically asymptomatic & does not require aggressive correction of electrolytes. They do very well with ORS & fluid correction as recommended by W.H.O.